Measuring Public Procurement Rules and Practices : Benchmarking a Recurrent Infrastructure Contract - Nogues Comas, Antoni Albert; Mendes dos Santos, Nuno Filipe (World Bank, Washington, DC, 2021)
Given its size, public procurement matters for economic development. Transparency, competition, accountability, efficiency, and innovation are most commonly noted as guiding principles for achieving best value for money in public contracts. Yet, large-scale, frequently updated, and comparable data on public procurement processes are scarce. This paper presents the methodology and findings of a new global indicator that benchmarks public procurement regulations and practices across 191 economies. The indicator proposes three dimensions to measure the effective implementation of public procurement systems in practice, as applied to a standardized recurrent infrastructure (roads) contract. The three dimensions include the steps and associated time required to complete the procurement process, and the availability and sophistication of e-procurement platforms. A final, fourth component benchmarks the regulatory framework applicable to such contracts. Economies that score higher in the indicator are those with more effective governments, higher quality of roads, and smaller perceptions of corruption. Looking more closely at the scores along the four dimensions reveals that countries differ to a lesser extent in terms of regulatory practices, compared with the use of new technologies such as e-procurement, where considerable gaps between economies exist.